2017
DOI: 10.1016/j.pedhc.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Youth-Centered Sexual Risk Event History Calendar (SREHC) Assessment on Sexual Risk Attitudes, Intentions, and Behavior

Abstract: Introduction The purpose of this study is to examine the effect of a youth-centered assessment, the sexual risk event history calendar (SREHC), compared to the Guidelines for Adolescent Preventive Services (GAPS) assessment, on sexual risk attitudes, intentions, and behaviors. Methods The Interaction Model of Client Health Behavior guided this participatory research-based randomized control trial. Youth participants recruited from university and community clinics in the Midwest were randomized to a healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
7
0
4
Order By: Relevance
“…The calendar is used to guide the interaction between the youth and clinician. The use of the calendar, developed in the United States, has resulted in more positive intentions to use condoms, possibly explained by the visual format encouraging the youths to reflect on their risk behaviour and by facilitating youth-provider communication [88].…”
Section: Sexual Risk Assessmentsmentioning
confidence: 99%
“…The calendar is used to guide the interaction between the youth and clinician. The use of the calendar, developed in the United States, has resulted in more positive intentions to use condoms, possibly explained by the visual format encouraging the youths to reflect on their risk behaviour and by facilitating youth-provider communication [88].…”
Section: Sexual Risk Assessmentsmentioning
confidence: 99%
“…O cuidado voltado a promoção da saúde da adolescente pode aparecer como um desafio para o profissional enfermeiro (Santos et al, 2020), principalmente quando a adolescente se torna mãe, o que aponta a necessidade de ferramentas que apoiam o estabelecimento do processo comunicativo (Munro-Kramer et al, 2017).…”
Section: Introductionunclassified
“…Assim, com os domínios do EHC podem ser levantados dados de diferentes dimensões de vida, como comportamentos, atividades realizadas, eventos e transições vivenciados (Martyn & Belli, 2002), em busca de uma abordagem centrada no sujeito (Munro-Kramer et al, 2017). Nesse sentido, emergiu a questão norteadora do estudo: "Quais elementos metodológicos podem ser utilizados para a construção dos domínios da ferramenta EHC?…”
Section: Introductionunclassified
“…Additionally, alcohol consumption is common for Ugandan adolescents and subsequently linked to other behaviors that can impact health including sexual risk behaviors (7,8). Seeley et al (9) found that being young (age [13][14][15][16][17][18][19][20][21][22][23][24] and participating in other risky behaviors (alcohol use, cigarette smoking) was associated with increased prevalence of HIV infection in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…The EHC has also been adapted for pregnancy (19) and eating and activity patterns for families (20). Finally, the EHC was tested against the Guidelines for Adolescent Preventive Services assessment in a randomized control trial in the clinical setting, demonstrating its clinical and research efficacy (17,21).…”
Section: Introductionmentioning
confidence: 99%